1966
DOI: 10.1515/iral.1966.4.1-4.85
|View full text |Cite
|
Sign up to set email alerts
|

An Experiment in Teaching a Second Language

Abstract: We are indebted to Father E. P. Dineen, Head ofthe German Dept. at Georgetown University, for making the experimental test possible.3 ) A first version of the German program was written by Irene Jones und er the supervision of C B. Ferster. M. I. Rocha e Silva was responsible for a radical revision, extension of the content and scope of the program, and the empirical trial at Georgetown University. C B. Ferster was responsible for the functional analysis of verbal behavior and its extension to the program cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…With speaking and instruction-following, this collateral instatement of new skills has not convincingly been shown in children learning grammatical skills in their first language (Lee, 1981). But it has been shown in adults learning second-language skills (Rocha e Silva & Ferster, 1966). The question raised by such collateral instatement of new skills is how subjects get from one repertoire to the other when there is no physical basis for response induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With speaking and instruction-following, this collateral instatement of new skills has not convincingly been shown in children learning grammatical skills in their first language (Lee, 1981). But it has been shown in adults learning second-language skills (Rocha e Silva & Ferster, 1966). The question raised by such collateral instatement of new skills is how subjects get from one repertoire to the other when there is no physical basis for response induction.…”
Section: Discussionmentioning
confidence: 99%
“…This discussion suggested that chained practice of spelling let the present subjects get from reading to spelling. Perhaps chained practice in getting from listening to speaking accounted for the collateral instatement of speaking in adults (Rocha e Silva & Ferster, 1966). If so, then the possibility exists of teaching this skill of "translating" between the two repertoires to children who have yet to learn it, so that they can "self-control" their acquisition of grammatical skills in one repertoire collateral to training in the other.…”
Section: Discussionmentioning
confidence: 99%
“…Several behavior-analytic studies have evaluated the efficacy of different procedures to teach rudiments of a second language to typically developing children (e.g., Cao & Greer, 2019;Davidson & O'Connor, 2019;Dounavi, 2011;May, Downs, Marchant, & Dymond, 2016;Petursdottir & Haflidadóttir, 2009;Petursdottir, Ólafsdóttir, & Aradóttir, 2008;Rosales, Rehfeldt, & Huffman, 2012;Rosales, Rehfeldt, & Lovett, 2011) and adults (e.g. Dounavi, 2013;Rocha e Silva & Ferster, 1966). Some of these studies investigated the extent to which learners (children or adults) may derive novel intraverbals when other relations are reinforced (cf., Dounavi, 2011;Petursdottir & Haflidadóttir, 2009;Petursdottir, Ólafsdóttir et al, 2008).…”
mentioning
confidence: 99%
“…This literature applies emergent learning practices and verbal operants to foreign vocabulary training (Daly & Dounavi, 2020 ). The languages taught include Native American (Haegele et al, 2011 ), Japanese (Petursdottir et al, 2014 ), French (Daly & Dounavi, 2020 ; Polson et al, 1997 ; Polson & Parsons, 2000 ), German (Rocha e Silva & Ferster, 1966 ), Spanish (Joyce & Joyce, 1993 ; Matter et al, 2020 ; Petursdottir et al, 2008 ; Ramirez et al, 2009 ), Italian (Petursdottir & Hafliđadóttir, 2009 ), Chinese (Wu et al, 2019 ), Welsh (May et al, 2016 , 2019 ), and English (Cortez et al, 2020 , 2021 ; Dounavi, 2011 , 2014 ; Rosales et al, 2011 , 2012 ). This literature’s defining feature is its focus on emergent learning as a critical outcome of effective foreign language instruction.…”
mentioning
confidence: 99%
“…Instead, the instructor expects untrained operants to emerge following a carefully selected subset of learning content (Critchfield, 2018 ; Dixon & Stanley, 2020 ). Studies in this field have implemented training procedures involving a range of verbal operants, including listener behavior (e.g., Rocha e Silva & Ferster, 1966 ), echoics (e.g., Petursdottir et al, 2014 ), mands (e.g., Wu et al, 2019 ), native-to-foreign intraverbals (NFI; e.g., Petursdottir & Hafliđadóttir, 2009 ), foreign-to-native intraverbals (FNI; e.g., Polson & Parsons, 2000 ), and tacts (e.g., Petursdottir et al, 2008 ) and tested for the emergence of untrained verbal operants.…”
mentioning
confidence: 99%